Adolescent self-injury: a comprehensive guide for counselors and health care professionals - D'Onofrio, Amelio A. (Springer Publ. Co., 2007)
The context and features of adolescent self-injury -- The experience of trauma and the foundations for self-injury -- The developmental effects of complex trauma -- The phenomenology of self-injury : the attempt to turn pain into self-healing -- Engaging the self-injurer : making contact with the person behind the behavior -- Assessing self-injury and the self-injurious adolescent -- From self-injury to health : an overview of the treatment process -- Managing self-injury in the school and on the college campus